Mitral Valve Regurgitation: A Severe Complication following Left Ventricular Biopsy 15 Years after Heart Transplantation - Marcel Vollroth; Joerg Seeburger; Philipp Kiefer; Jens Garbade; Friedrich W. Mohr; Markus J. Barten (Case Reports in Transplantation)
A 71-year-old male patient underwent orthotopic heart transplantation in 1995. Due to left heart catheterization 15 years later, biopsy from the left ventricular apex was performed for rejection screening. Two days later, echocardiography revealed severe mitral valve regurgitation requiring mitral valve replacement. This is a very rare case showing that left heart biopsy may lead to severe hemodynamic complications with the need for surgical intervention.